Give us today our daily bread: towards a phenomenological theology of embodied finitude - Heuslein, Jeremy (Practical theology, 2023)
In order to develop a phenomenological theology of embodied finitude, I first turn to the not-uncontroversial concept of kenosis. Drawing on the kenosis hymn in Philippians 2, as well as feminist and Eastern Orthodox thought, I argue for a relational understanding of kenosis that does not correspond to the conventional ‘self-emptying’ of kenotic theology. This is, in part, due to the experience of embodiment, which I turn to in my second section. Drawing upon phenomenological resources to articulate the nature of the embodiment as flesh, I argue that the intersubjective and interrelated constitution of the flesh grounds an understanding of kenosis and begins to articulate what embodied finitude is. I bring into this conversation the notion of ‘deep incarnation’, which reveals one of the depths of finitude: bodily need. In my final section, I explicate a reading of the Lord’s Prayer as part of a spirituality that embraces embodied finitude and incarnate need. Here, I distinguish between need and desire, with relational kenosis aiming at plerosis, that is, human flourishing as love.